Physical biochemistry - David Sheehan (Wiley-Blackwell, 2009)
The new edition of this successful textbook explains the basic principles behind the key techniques currently used in the modern biochemical laboratoryIt bridges the gap between general biochemistry textbooks and the more specialist books covering individual techniques.